2012
DOI: 10.1007/s10517-012-1817-2
|View full text |Cite|
|
Sign up to set email alerts
|

Repeated Moderate Stress Stimulates the Production of Dehydroepiandrosterone Sulfate (DHEAS) and Reduces Corticosteroid Imbalance in Old Macaca Mulatta

Abstract: Young (6-8 years) and old (21-30 years) Macaca mulatta females were subjected to gentle immobilization (2 h daily at 15.00) for 10 days. Blood specimens were collected before the exposure and 15, 30, 60, 120, 240 min and 24 h after the beginning of exposure on days 1, 3, and 10. The adrenocortical reaction to stress was maximum on day 1 in all animals. The increase of cortisol (F) and dehydroepiandrosterone sulfate (DHEAS) concentrations in young monkeys decreased on days 3 and 10, DHEAS drop being less pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In nonhuman primates, Goncharova et al [] found an increased cortisol/DHEAS ratio in depressed rhesus monkeys. A recent study also demonstrated that chronic moderate stress stimulated the production of DHEAS and reduced corticosteroid imbalance in old rhesus monkeys [Goncharova et al, ]. We suggest that initially, the body's response to stress is to increase production of both GC and DHEAS.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In nonhuman primates, Goncharova et al [] found an increased cortisol/DHEAS ratio in depressed rhesus monkeys. A recent study also demonstrated that chronic moderate stress stimulated the production of DHEAS and reduced corticosteroid imbalance in old rhesus monkeys [Goncharova et al, ]. We suggest that initially, the body's response to stress is to increase production of both GC and DHEAS.…”
Section: Discussionsupporting
confidence: 64%
“…Another adrenal hormone, dehydroepiandrosterone (DHEA) and its sulfated version (DHEAS) have been the focus of investigation as stress markers in humans [Du et al, ] and nonhuman primates [Goncharova et al, ; Maninger et al, ]. In mice, DHEA has been suggested to act as an anti‐stressor [Hu et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the effort to improve our ability to detect functional changes related to environmental stimuli, several authors have recommended the utility of exploring proportions, as opposed to individual values, of interconnected biological responses to specific systems, such as the HPA axis (Dhabhar, 2014;McEwen, 2018;Lambert et al, 2020;. Although in this study we did not investigate the mechanism of actions able to explain this relationship, thus limiting considerably our ability to further speculate, previous works have revealed that DHEA can enhance neuroprotection by decreasing glucocorticoidinduced apoptosis in various key brain areas, including the amygdala and hippocampus, and to promoting neurogenesis in the dentate gyrus (Maninger et al, 2009;Morgan et al, 2009;Goncharova et al, 2012). Therefore, these mechanisms could be the basis of the enhanced negative feedback Fig.…”
Section: Discussionmentioning
confidence: 96%
“…6,7,14 Physiologic resilience, defined as the ability of the organism to adapt to allostatic loads without permanent negative consequences, 35 has been associated with an enhanced negative feedback system regulating stress neurochemicals, as well as a form of cognitive reappraisal of stressful events. 21 In particular, DHEA is released in parallel with glucocorticoids (including corticosterone) during physical stress, 22 and has been associated with buffering against the negative effects of chronic stress. 40 Potentially related to the enhanced emotional resilience we found in the current study is that DHEA can act centrally to decrease glucocorticoid-induced neuronal death in the hippocampus and to promote neurogenesis in the dentate gyrus of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%